(untitled) (Proceedings of International Conference on Special Education, 2015)
In the light of Inclusive Education, the presence of comprehensive programs for the gifted and talented (PGT) learners in all levels of basic education is warranted to respond to their specific educational needs. This paper explored PGT in the Philippines through the frame provided by the harmonized definition of Philippine Inclusive Education gleaned from the focus group discussions and workshops conducted, and within the context of the K-12 system which is characterized with inclusiveness. Existing PGT, consistent with Philippine policy, emphasize specialization in the areas of science and technology, arts and sports. Except for sports, specialized high schools have been established to further content knowledge and competencies within specialized tracks that eventually lead into related professions. Workshop participants indicated the diverse needs of those under the gifted label. Questions regarding how the gifted from indigenous communities, identified gifted who are underachieving, the twice-exceptional, and gifted students enrolled in special schools who intend to pursue other interests alongside their specialized tracks, can be given programs that allow them to meet their potential. Implications of the new frame of inclusiveness would entail a deeper study of the identification process at the elementary levels, nature of support services needed, and the enhancement of the General Education program.